Germination ecology of southern crabgrass (Digitaria ciliaris) and India crabgrass (Digitaria longiflora): two important weeds of rice in tropics - Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2008)
Southern and India crabgrass are important grass weeds of rice in many tropical countries. Environmental factors influenced seed germination and seedling emergence of these weeds. Seeds of both species germinated at a range of alternating temperatures (25/15, 30/20, and 35/25 C day/night), though the germination of southern crabgrass was reduced at the lowest alternating temperatures (25/15 C). Light stimulated germination of both species; however, a small proportion of southern crabgrass seeds germinated in the dark. Germination of India crabgrass was influenced to a greater degree by increasing salt and water stresses than was southern crabgrass. Seeds of both species germinated over a wide range of pH between 5 and 10. Seedling emergence of both species (98% for southern crabgrass and 94% for India crabgrass) was greatest for seeds placed on the soil surface. Seed burial depth of 2 cm completely inhibited emergence of India crabgrass, whereas for southern crabgrass, this depth was 8 cm. Knowledge gained from this study is expected to contribute to developing components of integrated weed management strategies for these species.